PERANAN TIM LIKUIDASI DALAM RANGKA LIKUIDASI BANK - YOGA, I MADE DARMADI; Dharmakusuma, A.A. Gede Agung; KASIH, Desak Putu Dewi (Kertha Wicara : Journal Ilmu Hukum; Vol 1 No 01 (2012), 2012)
The role of banks in society today is very important and strategic, given the bank as a financialinstitution and is the measure of a country's financial system. Strategic role is a primary function ofbanks as institutions that can raise and channel public funds effectively and efficiently with ° Basedon economic democracy, to support the implementation of development nasional. Bank is afinancial institution which is where people save their money solely based on the belief that moneywill be recouped in time and with benefits such as interest. With the increasing number of bankstoday resulted in increased competition among banks. Of competition there are indications that leadto the banks less competitive behavior affects the health of the banks concerned eventuallyexperienced bankruptcy because of bad credit. The presence of large amounts of bad loans willcertainly bring banks to the struggling bank liquidation so that there was a problem.Based on the description of the background of the above it can be stated the following researchquestion: How does the role of the team in the process of liquidation of the bank's liquidation inaccordance with applicable law and the position of directors How bank after bank liquidation teamsetting?Problem solving is a very important role in the Liquidation Team bank liquidation process.Liquidation Team has the authority to perform maintenance tasks on the liquidated banks settle therights and obligations of the bank. Of arrangements made Liquidation Team is expected to providemaximum protection against the interests of bank creditors, while the bank's board of directorsposition after setting the Liquidation Team is to assist the team in completing the task managementliquidation of banks in liquidation and can be held responsible, together with shareholders terms ofthe elements found errors and omissions of the Board of Directors resulting bank license has beenrevoked and liquidated.
Keywords: Bank, Liquidity, financial, bankruptcy